Potential Positive Effects using Coenzyme Q10 Supplement as Adjuvant Therapy to Gabapentin for Managing Diabetic Neuropathy - Mohammed, Mohammed Mahmood; AbdulKareem Hadi , Rusul; Noori Salman , Isam (Iraqi Journal of Pharmaceutical Sciences, 2022)
The most prevalent chronic complication of diabetes mellitus is diabetic neuropathy. The pathogenesis of diabetic neuropathy is exacerbated by hyperglycemia-induced oxidative stress, which causes nerves to deteriorate in a programmed manner. Many clinical trials depend on supplement in an attempt to improve neuropathy symptoms such as (pain & tingling) and patient quality of life, one of them is Coenzyme Q10 which is reported to have an anti-inflammatory and antioxidant effects, and was totally nontoxic and non-reported side effects. This study aimed to evaluate using a Coenzyme Q10 supplement as an adjuvant therapy to gabapentin to improve the clinical symptoms of diabetic neuropathy in relation to its anti-inflammatory and antioxidant effects. This open-label interventional study involved 33 diabetic neuropathy patients divided into two groups: group (1) 16 patients were given 300 mg of gabapentin once a day at evening, plus group (2) 17 patients received 300 mg of gabapentin once a day in the evening plus Coenzyme Q10 200mg once daily. Pre- and post-3 months of treatment, blood samples used to measure metabolic, anti-inflammatory and antioxidant biomarkers (fasting blood glucose, glycated hemoglobin, tumor necrosis factor-α, Iinterleukin-6 & Superoxide dismutase) , as well as the Michigan neuropathy screening instrument for assessment of clinical symptoms. After 3 months of Coenzyme Q10 use, the results showed that the group 2 produced a highly significant change in glycated hemoglobin & fasting blood glucose levels. Meanwhile, there is no significant change in glycated hemoglobin & fasting blood glucose values in patients receiving just gabapentin. Moreover, results showed highly significant differences in Michigan neuropathy screening instrument, tumor necrosis factor-α, iinterleukin-6 & superoxide dismutase between the study groups at the completion of the research. Finally, addition of Coenzyme Q10 to gabapentin for diabetic neuropathy patients result in improving the glycemic control & symptoms of the diabetic neuropathy, as well as decreasing effects of the inflammation in addition to oxidative stress after three months of treatment.